Assessment of the effectiveness of biological and pharmacological support for training at the preparatory stage for handball players - Favoritov, V.; Gostishchev, V. (Slobozhanskyi herald of science and sport, 2019)
Based on the analysis of the biological and pharmacological support of athletes, a dietary supplement was chosen to study the effectiveness of the application at the preparatory stage. The presented experimental data indicate that there are positive significant differences between the control and experimental groups of athletes who took dietary supplements of NSP Defense Maintenance. The conducted studies confirm the need for planning the biological and pharmacological support of sports activities in order to increase sports results and prevent and restore athletic health and athletic disabilities.